Evil Dead 2: Dead By Down - Sam Raimi; Dan, Hicks; Denise Bixler; Kassie DePaiva; Richard Domeier; Sarah Berry; Ted Raimi; Bruce Campbell (USA De Laurentiis Entertainment Group, 1987)
A sequel/remake of the film The Evil Dead. A young man named Ash takes his girlfriend Linda to a secluded cabin, and plays back a professor's tape recorded recitation of passages from the Book of the Dead. The spell calls up an evil force from the woods which turns Linda into a monstrous Deadite, and threatens to do the same to Ash. When the professor's daughter and her entourage show up at the cabin, the night turns into a non-stop, grotesquely comic battle with chainsaw and shotgun on one side, demon horde and flying eyeball on the other.
A man is trapped in a cabin with a group of strangers, while being attacked by flesh-possessing demons.
Sam Raimi
Language(s): English
Subtitle(s): English, Turkish, Spanish, Italian, Dutch, Portoguese
Keywords: Comedy; Fantasy; Horror; Action